Language ideologies in the Chinese context orientations to English as a Lingua Franca - Wang, Ying (De Gruyter Mouton, 2020)
This book explores language ideologies in China, which encounters the unprecedented global spread of English as a lingua franca, against the backdrop of globalisation where China emerges as a rapidly developing economy with vigorous promotion of Chinese around the world. The book addresses Chinese speakers' ideologies in relation to ELF and provides insights into non-native English speakers' engagement in the development of English in the future
Keywords: China; Chinese English as a Lingua Franca (ChELF); ELF orientations; Englisch als Lingua Franca; Language Ideology; Language Legitimacy; Sprachplanung; Sprachpolitik; LANGUAGE ARTS & DISCIPLINES / Linguistics / General; Ideologie; Englisch; Verkehrssprache